Four shades of paternalism in doctor–patient communication and their ethical implications - Fleisje, Anniken (Bioethics, 2024)
The present study aims to explore the forms paternalistic communication can take in doctor–patient interactions and how they should be considered from a normative perspective. In contemporary philosophical debate, the problem with paternalism is often perceived as either undermining autonomy (the autonomy problem) or the paternalist viewing their judgment as superior (the superiority problem). In either case, paternalism is problematized mainly in a general, theoretical sense. In contrast, this paper investigates specific doctor–patient encounters, revealing distinct types of paternalistic communication. For this study, I reviewed videorecorded encounters from a Norwegian hospital to detect paternalism—specifically, doctors overriding patients' expressed preferences, presumably to benefit or protect the patients. I identified variations in paternalistic communication styles—termed paternalist modes—which I categorized into four types: the fighter, the advocate, the sympathizer, and the fisher. Drawing on these findings, I aim to nuance the debate on paternalism. Specifically, I argue that each paternalist mode carries its own normative implications and that the autonomy and the superiority problems manifest differently across the modes. Furthermore, by illustrating paternalism in communication through real-life cases, I aim to reach a more comprehensive understanding of what we mean by paternalistic doctors.